Estudo experimental dos efeitos do canabidiol: possível estratégia para o tratamento da adição à anfetamina - Metz, Vinícia Garzella (2022)
Amphetamine (AMPH) addiction is a chronic and relapsing disease caused by the compulsive drug seeking and continued use despite harmful consequences. Currently, there is no effective and approved pharmacological treatment for the treatment of this important neuropsychiatric condition. Thus, the search for new therapeutic targets that can favor the treatment of drug addiction and reduce recurrent relapses represents the biggest challenge for the cure of the condition. Cannabidiol (CBD) has shown many benefits in the treatment of diseases that affect the central nervous system and recently, it has been considered a potential strategy for the treatment of addiction.Thus, the present study aimed to evaluate the effects of CBD on neurochemical and behavioral parameters of relapse in rats AMPH-exposed, whose execution involved two experimental protocols. In experimental protocol 1 (EP1), the effects of CBD treatment on behavioral parameters of relapse after conditioning and reconditioning with AMPH after drug preference extinction were evaluated. In that protocol, animals were initially exposed to ANF (4 mg/kg, i.p) in the conditioned place preference (CPP) protocol for 8 days. After the CPP test, the animals received CBD treatment (5 or 10 mg/kg, i.p) during the 5 days of drug abstinence. Subsequently, the animals were exposed again to AMPH (reconditioning) for 3 days and the relapse test was performed. In experimental protocol 2 (EP2), the aim was to investigate the effects of CBD treatment on behavioral parameters of relapse to AMPH induced by a stressor stimulus. For this, the animals were exposed to AMPH(4 mg/kg, i.p) through the CPP protocol for 8 days and sequentially treated with CBD (10 mg/kg, i.p) during the 5 days of drug abstinence. Relapse drug-seeking behavior was induced by a forced swimming protocol prior to relapse testing. In both protocols, the animals were also submitted to behavioral assessments in the open field test and elevated plus maze to analyze locomotor activity and anxiety behaviors, respectively. Furthermore, in PE1, the prefrontal cortex (PFC) and ventral striatum (EV) were collected for the analysis of dopaminergic targets through western blot, while in PE2, the regions chosen were the ventral tegmental area (VTA) and the EV for the analysis of dopaminergic and endocannabinoid targets. Our results showed that, in both experimental protocols, CBD prevented AMPH relapse and decreased anxiety behavior per se, also observed in animals exposed to AMPH. In EP1, CBD restored the levels of dopaminergic targets (D1R, D2R, DAT and TH), altered by AMPH exposure in both brain regions.This same effect of CBD on D1R, D2R and DAT in VE was observed in EP2. Molecular analysis of EP2 also revealed that in VTA, CBD restored CB1R levels lowered by AMPH exposure, increased levels of the enzyme responsible for endocannabinoid synthesis, NAPE-PLD, and decreased levels of the enzyme that degrades them, the FAAH. These molecular findings allow us to hypothesize that the potential anti-relapse effect of CBD reflects its ability to increase endocannabinoid tone and thus restore the dopaminergic system compromised by AMPH exposure. Although further studies are needed, CBD appears to be a promising pharmacological alternative for the treatment of addiction to psychostimulant drugs such as AMPH.